Multiple heavy metals immobilization based on microbially induced carbonate precipitation by ureolytic bacteria and the precipitation patterns exploration. (July 2021) - Qiao, Suyu; Zeng, Guoquan; Wang, Xitong; Dai, Chenggang; Sheng, Mingping; Chen, Qun; Xu, Fei; Xu, Heng
Abstract: Biomineralization to immobilize the toxic metal has great potential for the bioremediation of multiple heavy metal contamination. In this study, the efficiency of Microbially Carbonate Induced Precipitation (MICP) for several common heavy metals (Cu, Zn, Ni, Cd) in mining areas as well as their precipitation patterns were researched. After urease activity and precipitation ability comparison, Sporosarcina kp-4 and kp-22 were selected for subsequent studies. The removal of Cd was mainly based on the formation of cadmium carbonate induced by bacteria activity, while the removal of Cu was depended on the pH increase generated by the same process. Precipitation contributed to Zn and Ni removal was more complex, which was also based on the MICP process. Removal rates of Cu, Zn, Ni, and Cd (the concentration of all metals was 160 mg/L) reached 75.10%, 98.03%, 59.46% and 96.18%, respectively, within 2 h. For the immobilization of Cu, Zn, Ni and Cd at 160 mg/L, the optimal dosages of bacterial cultured solution were about 0.25 mL, 0.8 mL, 0.5 mL and 0.8 mL, respectively. Minimum inhibitory concentrations (MIC) revealed the toxicity of these heavy metals for MICP bacteria was arrange as: Cd > Zn > Ni > Cu. Our study confirmed that urease-producing bacteria could coprecipitate multiple heavy metals even without the ability tolerate them, and the MICP process was an effective biological approach that was worth investigating further to immobilize multiple heavy metals in ecological restoration. Highlights: Urease tolerance to heavy metals was more important during immobilization. Precipitated pattern of MICP contained environmental supersaturation. The dosage of bacterial cultured solution played a key role in immobilization. Precipitate could redissolve due to the excessive use of bacteria except Cd.